Targeting of DEC-205 on human dendritic cells results in efficient MHC class II-restricted antigen presentation - Birkholz, Katrin; Schwenkert, Michael; Kellner, Christian; Gross, Stefanie; Fey, Georg; Schuler-Thurner, Beatrice; Schuler, Gerold; Schaft, Niels; Dörrie, Jan (Blood, 2010)
The use of dendritic cells (DCs) in therapeutic cancer vaccination requires their loading with tumor-specific antigen(s). DEC-205, a phagocytosis receptor mediating antigen uptake, is associated with CD8+ T-cell responses in mice. Here we fused an anti-DEC-205scFv to an HLA-DP4-restricted epitope from the tumor antigen MAGE-A3, and examined the suitability and efficacy of DEC-205 to deliver a helper epitope to human monocytederived DCs (moDCs). The construct specifically bound DEC-205 on human moDCs without negative impact on DC phenotype and function. We measured antigen presentation with specific autologous CD4+ T cells, generated by TCR-RNA transfection. DEC-205 targeting resulted in significant major histocompatibility complex class II-restricted antigen presentation, and was superior to loading DCs by electroporation of mRNA encoding endosome-targeted MAGE-A3-DCLAMP or by direct peptide pulsing. Anti-DEC-205scFv-MAGE-A3 was presented 100 times more efficiently than the control constructs. DC maturation before or during incubation with anti-DEC-205scFv-MAGE-A3 reduced the interleukin-10/interleukin- 2 ratio. Moreover, we successfully applied the DEC-205 targeting strategy to moDCs from malignant melanoma patients. Again, DEC-205-targeted mature DCs (mDCs) presented the antigen more efficiently than peptide-pulsed DCs and maintained their stimulatory capacity after cryoconservation. Thus, DEC-205 targeting represents a feasible and effective method to deliver helper epitopes to DCs in anticancer vaccine strategies, which may also be suitable for DC targeting in vivo. © 2010 by The American Society of Hematology.
CRIS-Team Scopus Importer:2021-10-01